What determines logistics sub-degree students' decision to pursue a bachelor's degree? (UCL Press, 2022)
With the growing importance of the logistics industry and the increasing demand for logistics professionals with a bachelor's degree qualification, the government and industry in China have long been looking for ways to attract more logistics sub-degree students to pursue higher education. This article aims to provide insights into the factors that determine logistics sub-degree students' intention to pursue a bachelor's degree. The study extended the theory of reasoned action (TRA) model to include four variables, namely perceived difficulty, job opportunities, job starting salary and genuine interest. The findings from the study involving 361 logistics sub-degree students from three institutions show that logistics sub-degree students' decision to pursue a bachelor's degree is determined by attitude, subjective norm, perceived difficulty, job opportunities, job starting salary and genuine interest. Genuine interest is identified as a new precursor of intention. The findings also show that there is a significant difference between students from different types of programmes. Based on the findings, this article proposes some measures for the relevant parties to motivate and attract logistics sub-degree students to further their study at bachelor's degree level.